THE PEDAGOGICAL IMPARTIALITY REQUIREMENT IN QUEBEC’S ETHICS AND RELIGIOUS CULTURE CURRICULUM: IS IT CONSISTENT WITH TEACHER AUTONOMY AND CHARTER RIGHTS? - Maxwell, Bruce (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
Quebec’s Ethics and Religious Culture program (ERC) requires teachers to adopt a professional stance of pedagogical impartiality. This article examines the complex regulatory framework surrounding the impartiality requirement from the perspectives of teachers’ legally recognized right to professional autonomy, their constitutional rights to religious freedom and freedom of expression, and the related issue of impartiality as a pedagogical device when teaching about controversial issues. The paper’s brief review of the jurisprudence does not support a decisive answer to the question of whether the legal basis of the impartiality ERC’s impartiality requirement is sound. However, it does reveal that the impartiality requirement is more legally fragile than it might appear at first glance. L’EXIGENCE D’IMPARTIALITY EN ÉTHIQUE ET CULTURE RELIGIEUSE : EST-ELLE CONFORME À L’AUTOMIE PROFESSIONNELLE DES ENSEIGNANTS ET LES DROITS GARANTIS PAR LA CHARTE? Le programme d’Éthique et culture religieuse (ÉCR) impose à ceux qui l’enseigne une obligation d’assumer une posture professionnelle empreinte d’impartialité. Cet article propose une analyse de l’encadrement réglementaire entourant cette exigence d’impartialité du point de vue du droit des enseignants québécois à l’autonomie professionnelle, leur droit constitutionnel à la liberté d’expression et à la liberté religieuse et l’enjeux connexe de l’impartialité enseignante comme un outil pédagogique disponible aux enseignants lorsqu’ils abordent des questions sensibles en classe. L’examen de la jurisprudence proposé dans ce texte laisse la question ouverte quant à la validité juridique de l’exigence d’impartialité. Cependant, tout indique que l’encadrement réglementaire lié à l’exigence d’impartialité en ÉCR comprend de sérieuses lacunes.